Juridical Analysis of Judges' Considerations in Denying the Rights of Restitution to Victims of Human Trafficking Crimes (Study Decision No. 359 / Pid.Sus / 2020 / PN Cbi) - Dharmawan, Nancy Natalia; Santoso, Aris Prio Agus; Aryono, Aryono (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
The implementation of providing restitution is not easy for the court to grant. assist in fulfilling the rights of restitution to victims because prosecutors in carrying out loans have difficulty presenting evidence of expenditure to determine the size of compensation. Settlement case No. 359 /Pid.Sus/2020/PN Cbi is one of the cases where the panel of judges rejected the request for restitution requested by public submission. This research aims to determine the legal provisions governing restitution as a right for victims of human trafficking crimes in Indonesia, analyze the considerations of judges who deny the right to restitution for victims of TIP and enforce the judge's decision that refuses to grant the right to restitution for victims of TIP in the case of Decision No. 359 / Pid.Sus / 2020 / PN Cbi. This research is included in normative juridical research with data obtained from literature studies or library research. The results of this research are that the legal provisions governing restitution as a right of victims of criminal acts of human trafficking in Indonesia are regulated in Article 48 of Law 21/2017 which basically regulates a series of mechanisms for implementing provisions for providing restitution for criminal acts of human trafficking. The panel of judges was correct in providing a legal opinion in rejecting the request for restitution. This causes general lending to not follow the terms, procedures and procedures for requests for restitution, and the panel of judges cannot decide on its own general order regarding the amount of restitution without being based on the provisions regarding restitution which are considered correct and in accordance with applicable regulations so that the panel of judges must request restitution. what is being requested is not in accordance with the applicable law and the impedance of a judge's sentence who refuses to grant a TIP victim the right to restitution. The victim will suffer either physical injury or physical or mental deterioration due to the absence of compensation given to him as a victim of the criminal act of trafficking in persons.